Flipped Learning in Computer Science for non-native English-speaking Students: Case Study - Paul Doyle; Melinda Szappanyos; Brian Gillespie; Cathy Ennis; Victor Rebay; Ryan Shapiro (Irish Journal of Academic Practice, 2022)
While flipped learning courses generally follow a basic concept (web-based technologies outside the classroom and instructor-student interaction during class time), the detailed design of the delivery builds on the instructor's personal experience, knowledge, teaching philosophy and goals of the course. When designing such a course, it is very important to also take into consideration the teaching and learning environment and culture of the students. Flipped learning is not a fully grounded category in education literature; the area has been examined by a number of studies, but the methodology and its concept is not completely standardized [1, 2]. The flipped learning concept reached the Republic of Korea (RoK) over a decade ago as a result of challenges East Asian universities were facing: to enhance the quality of education, to keep up with international trends and to make education as cost-effective as possible [3]. Tham and Tham [4] reviewed blended learning practices in higher education across Asia and noted that while there are a number of challenges in delivering blended modules in general, in Korea, there was much interest and approval for such a format. As a new, and in Western countries highly praised, methodology, it requires careful consideration and examination. Keeping in mind that Korean education methodology and students' school behavioural patterns are different from Western higher-education systems, this paper compares the recommendations made and features considered ideal by the literature, to the reality of a flipped learning course delivered in the RoK while acknowledging that there is no absolute recipe to a successful flipped learning course. It is also worth noting that this case study is also an intensive summery delivery of technical course material by a native English speaking lecturer to non-native English speaking students. The case study presented in this paper is the first flipped learning course examined in such a setting, with similar courses being developed for delivery in the near future. Therefore, lessons learned from this case study will help in designing and implementing courses in the future. Similarly, it is important to note that this case study pre-dates the Covid19 global pandemic (taking place in the Summer of 2019), meaning that social distancing and other related concerns were not relevant during delivery. However, knowing about the successes and challenges of such formats is of particular relevance to educators in more recent times, as we have become more reliant on blended/online teaching and learning. Based on our final findings presented in this case study it seems certain that the flipped learning methodology has a future in Korean higher education, as long as the course is designed for the specific setting: for example, emphasis should be put on student/teacher discourse in order to encourage naturally shy students to engage with the instructor, to increase constructive interaction throughout the course.